Advances in Multimedia Modeling 15th International Multimedia Modeling Conference, MMM 2009, Sophia-Antipolis, France, January 7-9, 2009. Proceedings. - Huet, Benoit; Smeaton, Alan; Mayer-Patel, Ketan; Avrithis, Yannis (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2009)
This book constitutes the refereed proceedings of the 15th International Multimedia Modeling Conference, MMM 2009, held in Sophia-Antipolis, France, in January 2009. The 26 revised full papers and 20 revised poster papers presented together with 2 invited talks were carefully reviewed and selected from 135 submissions. The papers are organized in topical sections on automated annotation, coding and streaming, video semantics and relevance, audio, recognition, classification and retrieval, as well as query and summarization.